Evaluation of Potential Environmental Impacts in the Agroecological Egg Production Chain Using a Life Cycle Assessment Approach - González-Velandia, Krystle Danitza (2020)
[Introduction]: Analysis of environmental impacts in egg production show significant differences between conventional and organic systems, associated with food, energy efficiency, distribution and waste management. However, the environmental impacts of agroecological egg production systems are unknown. [Objective]: to assess the environmental impacts of agroecological egg production using a life cycle analysis. [Methodology]: The study was performed for 350 Hy Line Brow hens from agroecological farms in Cundinamarca, Colombia. The analysis covered the entire production chain of 1 kg of eggs, that is, from the cradle to the grave, following the guidelines of ISO 14040. The information was collected during one-year, contemplating food production, production, distribution, consumption, and final disposal. Quantities of materials, energy, and waste were considered to evaluate the impacts with the CML-2001 methodology subsequently. [Results]: the outcome revealed that the environmental effects of an agroecological egg were up to 30% lower than those of a conventional egg. This result is mainly due to feed, which is produced in an agroecological way in the same farm; it is also due to waste treatment, use of alternative energy, and reduction of intermediaries along the commercial chain. [Conclusions]: Although the impacts of agroecological eggs are lower, it requires greater efficiency in nitrogen management, the search of disinfectants with lower impacts on the soil, the implementation of shorter and cleaner distribution systems, and the promotion of packaging material reuse.